2021
DOI: 10.1111/jvh.13611
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of prognostic models for predicting survival outcomes in Acute‐on‐chronic liver failure patients

Abstract: Acute-on-chronic liver failure (ACLF) is a syndrome characterized by acute decompensation of chronic liver disease associated with high bacterial infection (BI) and shortterm mortality. However, many ACLF prognostic predictive modelsare complicated.The aim of this study is to develop prognostic models for ACLF patients to predict BI and mortality. We retrospective recruited 263 patients with ACLF from Shandong Provincial Hospital and Taizhou Enze Medical Center (Group) Enze Hospital. ACLF was defined according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…INR and total cholesterol are important indicators of liver synthetic function. Similar to previous studies (15,16), these 2 indicators in this study were independent risk factors of mortality in patients with subacute liver failure. Therefore, it is necessary to observe the dynamic changes of these 2 indexes in the clinic and implement timely and effective interventions.…”
Section: Discussionsupporting
confidence: 91%
“…INR and total cholesterol are important indicators of liver synthetic function. Similar to previous studies (15,16), these 2 indicators in this study were independent risk factors of mortality in patients with subacute liver failure. Therefore, it is necessary to observe the dynamic changes of these 2 indexes in the clinic and implement timely and effective interventions.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, a few predictive models based on the immune-inflammatory and hepatic function indexes were also constructed to predict the infection development and prognosis in ACLF with limited predictive efficacy. Zhang Z and Rui et al reported that two predictive models (one named GIC including serum globulin, IL-6, and CRP; the other model including albumin, CRP, and glucose) can predict the bacterial infection development in HBV-ACLF patients 6 , 7 . Furthermore, some parameters, such as age, total bilirubin, lactate dehydrogenase, soluble IL-2 receptor, WBC count, etc., were also identified as independent predictors for mortality in ACLF patients with infection 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%